Dynamic Resistance Training Improves Cardiac Autonomic Modulation and Oxidative Stress Parameters in Chronic Stroke Survivors: A Randomized Controlled Trial. (20th November 2019) - Gambassi, Bruno Bavaresco; Coelho-Junior, Hélio José; Paixão dos Santos, Camila; de Oliveira Gonçalves, Ivan; Mostarda, Cristiano Teixeira; Marzetti, Emanuele; Sotão, Samir Seguins; Uchida, Marco Carlos; De Angelis, Kátia; Rodrigues, Bruno
Abstract : Stroke survivors are at substantial risk of recurrent cerebrovascular event or cardiovascular disease. Exercise training offers nonpharmacological treatment for these subjects; however, the execution of the traditional exercise protocols and adherence is constantly pointed out as obstacles. Based on these premises, the present study investigated the impact of an 8-week dynamic resistance training protocol with elastic bands on functional, hemodynamic, and cardiac autonomic modulation, oxidative stress markers, and plasma nitrite concentration in stroke survivors. Twenty-two patients with stroke were randomized into control group (CG, n = 11 ) or training group (TG, n = 11 ). Cardiac autonomic modulation, oxidative stress markers, plasma nitrite concentration, physical function and hemodynamic parameters were evaluated before and after 8 weeks. Results indicated that functional parameters (standing up from the sitting position (P = 0.011 ) and timed up and go (P = 0.042 )) were significantly improved in TG. Although not statistically different, both systolic blood pressure (Δ = − 10.41   mmHg ) and diastolic blood pressure (Δ = − 8.16   mmHg ) were reduced in TG when compared to CG. Additionally, cardiac autonomic modulation (sympathovagal balance–LF/HF ratio) and superoxide dismutase were improved, while thiobarbituric acid reactive substances and carbonyl levels were reduced in TG when compared to the CG subjects. In conclusion, our findings support the hypothesis that dynamic resistance training with elastic bands may improve physical function, hemodynamic parameters, autonomic modulation, and oxidative stress markers in stroke survivors. These positive changes would be associated with a reduced risk of a recurrent stroke or cardiac event in these subjects.